Synthesis of metal sulfides using Lawesson's reagent for photocatalytic hydrogen production. (2022) - Pandit, Vikram
Abstract: Lawesson's reagent (LR) is mainly used for converting ketones, amides, lactones and esters compounds into thiocarbonyls. In this paper, molybdenum sulfide (MoS2 ) a metal sulfides synthesis using hydrothermal reactor at 180 °C of 15 h. reaction time is reported. After complete synthesis the nanostructured MoS2 were characterized using X-ray diffraction (XRD), UV–visible, FESEM and TEM micrographs. FESM images of LR and showed the layered structures of nanostructured MoS2 . Transmission electron microscopy confirmed the formation of layered structures of MoS2 nanostructures. After characterization MoS2 nanostructures were tested for its photocatalytic behavior using hydrogen generation via water splitting, MoS2 we found 608.33 µmol/h/g of hydrogen. For this photocatalytic experiment a modest, easy to use, low cost, and easy to clean and ecofriendly photocatalytic hydrogen production setup is used.